AETIOLOGIC AGENTS AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN ASSOCIATED WITH URETHRAL CATHERTERISED PATIENTS AT THE FEDERAL MEDICAL CENTRE, UMUAHIA ABIA STATE, NIGERA - Odinaka, Iwu, Justus; Vincent, Otokunefor, Tosanwunmi; Blaise, Chikere, Chioma. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The increasing rate of catheter associated urinary tract infection (CAUTI) and the resistance inempirical antibiotic therapy became a threat to mankind. This study therefore identify microbialpathogens associated with bacteriuria and UTI in patients with indwelling urethral catheters anddetermine their susceptibility patterns to commonly used antimicrobial agents. A total of 1000urine specimens from 1000 patients were used in the study and analyzed for white blood cellcount and bacteria count. The specimens were cultured on Blood, MacConkey and CLED agarplates. Pure colonies of the isolated organisms were biochemically characterized and antibiogramwas performed on each of the bacterial isolate. The commonest indication for catheterization isbladder outlet obstruction (BOO, 30%) followed by Congestive cardiac failure (CCF, 15%).Seven hundred and eighty patients were urine culture positive for microbial pathogens with 684bacterial isolates, 96 (9.6 %) yeast while 220 (22%) were bacteriologically sterile. Patients above80years had the highest total bacterial count of 13.1 x 104 Cfu/ml followed by patients betweenthe age of 61 – 80 and 41 – 60 with total heterotrophic bacterial count of 12.1 x 104 Cfu/ml and13.1 x 104 Cfu/ml, respectively. Staphylococcus spp. were the commonest pathogens with 584isolates (85.4%), followed by Pseudomonas spp. 48 (7.0%), Klebsiella spp. 30 (4.4%),Escherichia spp. 15 (2.2%) and Proteus spp. 7 (1.0%). The invitro antibiotic susceptibilitypattern of the organisms presents a mixed response (susceptible / resistance) to commonly usedantibiotic s such as Ceftazidine, Cefurosime. Gentamycin, Cefuroxime, Nitrofurotoin,Ciprofloxacin, Cofrimoxazola, Cloxacilline, Erythromycin, Streptomycin, Tetracycline,Chloramphenicol, Augmentin, Ofloxacin. There is high level of resistance to antibiotics by theorganisms isolated and no single antibiotic used in the study was able to eliminate all the isolatesidentified. There is 100% resistance by all the organisms to Cotrimoxazole. Analysis of Variance(ANOVA) showed insignificant difference between means for the various parameters examinedat P ≤ 0.05.